Personal Christology: New Testament Positions and Perspectives - Brand, Aleksandra; Söding, Thomas (Biblische Zeitschrift - Supplements, 2025)
The New Testament characterises God as a “you” who should and can be loved; it describes Jesus as a person not only of the past, but also of the present and the future. In light of the belief in the resurrection and the expectation of the Second Coming, the New Testament sharpens the memory of Jesus. Its texts are testimonies of faith that are touched by the love of God and inspired by the love of Jesus Christ. In this volume, scholars examine a wide range of New Testament writings from the Gospels to the Revelation of John. In stylised biographies, in narrated stories and in reflected confessions, the New Testament writings make clear how challenging and critical, how exhilarating and inspiring encounters with God through encounters with Jesus are. They record characteristic encounters with Jesus, enlightened knowledge of faith and Spirit-filled songs of Jesus